An analysis of geography content in relation to geography for life standards in Oman. Issue 1 (2nd January 2018) - Al-Nofli, Mohammed Abdullah
ABSTRACT: Since the publication of Geography for Life: National Geography Standards in the United States (Geography Education Standards Project, 1994), it has been widely used to develop quality curriculum materials for what students should know and able to do in geography. This study compared geography content taught in Omani public schools with Geography for Life standards. Content analysis was used to analyze the extent to which the 18 standards were incorporated into the geography content. It focused on all discrete geography units included in social studies textbooks for Grades (3–10) and two geography textbooks: Economic Geography (Grade 11) and Geography and Modern Technologies (Grade 12). As the study revealed, geography content included good coverage of six standards, including those related to the environment and society. On the other hand, eight standards received less attention in the textbooks, including mental maps and the uses of geography. Findings of the study provided important implications for improving the geography curriculum in Oman.